The effects of some selected demographic characteristics on in-service teachers' views of nature of science and process skills - Shallow, Adisu Daniel; Tadese, Abebaw Lemma (Cadernos de Educação Tecnologia e Sociedade, 2021)
The objectives of this study were to explore in-service teachers’ views of the nature of science and process skills (NOS and PS), compare teachers’ views of NOS and PS in terms of some selected demographic variables such as gender, work experience, grade levels, and subjects they teach. In addition, measure the effect of these demographic variables on teachers’ views of NOS and PS. Cross-sectional descriptive survey employed. Convenience and purposive samplings used to select study subjects. Data collected by using VNOS- form D that modified by Ling et als in 2006. Frequency count, Kruskal Wallis Test, two-ways ANOVA, and multiple regressions used to analyze data. The findings indicated, in-service teachers had naïve views in nine or 39.1% questions out of 23 questions about NOS and PS. In comparing groups, there are significant difference in gender, work experience, and grade level they teach. From effect analysis, gender and work experience had significant effect on views of NOS. There is no significant interaction effect of all paired variables. The regression indicates, demographic characteristics had significant contributions on views of NOS and PS (F (4, 222) = 4.78, p = .001). Generally, the findings indicated, there is effect of demographic variables on teachers’ views of NOS, though it is small. Thus, when developing school curricula, integrating concepts related to NOS suggested in different level. In addition, when developing college curricula for in-service teachers, the effect of demographic characteristics on their views NOS and PS needs consideration. Therefore, may college and school curricula revision in terms of NOS. In addition, seminars, mentoring, and reflective readings suggested to minimize problems related to in-service teachers’ views of NOS and PS.